THE THE PERSPECTIVE OF BATIK WRITERS ON THE USE OF DYES AT THE GIRILOYO BATIK CENTRE, WUKIRSARI VILLAGE, IMOGIRI DISTRICT, BANTUL REGENCY, SPECIAL REGION OF YOGYAKARTA - Indriani, Rima; Adisty, Priskila; Primananda, Rizka (SERUNAI, 2025)
This study aims to examine the perspectives of batik artisans at the Giriloyo Batik Center regarding the use of dyes, both natural and synthetic, as well as their impact on the environment, health, and the sustainability of batik culture. The Giriloyo Batik Center, as one of the traditional batik centers in the Special Region of Yogyakarta, has local values and traditions that continue to be preserved by the artisans. Using a descriptive qualitative approach, data was collected through in-depth interviews, observations, and document studies. The research findings indicate that the choice of dyes used by batik artisans is not only influenced by aesthetic factors and production efficiency but also by an understanding of the long-term impacts on the environment and health. Some batik makers are beginning to switch to natural dyes, as they are considered more environmentally friendly and supportive of preserving traditional values. However, challenges remain regarding the availability of materials, longer production processes, and color durability. This study highlights the importance of education and support for environmentally friendly dyeing practices to ensure the sustainability of the local batik industry.